A responsabilidade do controle interno no combate à corrupção na administração pública federal: os resultados econômicos aferidos e a percepção de maturidade em projetos - Silva, Juscelino Ricardo Pereira da (2016)
Recognized as one of the biggest issues that disturb Brazil’s social and economic development, corruption is a social harm that any country committed with the defense of its economic interests and rule of the law must combat. For that purpose, in the Brazilian case, the Federal Public Administration, by means of the General Union Controller - CGU and the Federal Internal Control System, has played functions related to the various cases of misappropriation of money and corruption involving public resources under its sphere of responsibility. Being the internal control one of the tools utilized to reach that goals, evaluating its responsibility on corruption’s combat and whether the efficiency of the CGU acting runs by its level of maturity at projects, comparing it with the matureness of other public controllers, is the main factor of the research. The research’s results demonstrate that the relevance of the matureness’ indicator to establish the organ’s profile does not influence directly on its institutional mission, however, there are other aspects that contribute to the success of CGU on the playing of its activities